2016
DOI: 10.1590/1807-1929/agriambi.v20n3p250-255
|View full text |Cite
|
Sign up to set email alerts
|

Sampling plan for using a motorized penetrometer in soil compaction evaluation

Abstract: A B S T R A C TThis study aimed to estimate the size of blocks of observations of resistance to penetration, obtained by a motorized digital penetrometer, and the number of blocks with semiamplitude of the confidence interval between 5 and 20% of the mean penetration resistance, for different soil depth ranges and cone diameters. Data were collected in two contrasting plots of a crop-livestock integration experiment, located in Abelardo Luz, SC, Brazil. Ten blocks were delimited and the resistance to penetrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In all cases, the estimated sample sizes (Table 3) exceeded the sampling recommendations reported in other studies (Tavares Filho and Ribon, 2008;Molin et al, 2012;Storck et al, 2016). For example, the general recommendation of 20 samples would result in an estimation of the vertical profile of mean CI values with an error near ± 40 %, the 80 % of the times at best, independently of the estimator or the sampling time.…”
Section: Sample Sizementioning
confidence: 62%
“…In all cases, the estimated sample sizes (Table 3) exceeded the sampling recommendations reported in other studies (Tavares Filho and Ribon, 2008;Molin et al, 2012;Storck et al, 2016). For example, the general recommendation of 20 samples would result in an estimation of the vertical profile of mean CI values with an error near ± 40 %, the 80 % of the times at best, independently of the estimator or the sampling time.…”
Section: Sample Sizementioning
confidence: 62%
“…This result is due to higher variation in the SPR values in this soil layer, as was previously discussed for the item numbers of subsamples per sampling point. Tavares Filho and Ribon (2008) compared no-tillage and conventional tillage systems, and Storck et al (2016) studied an integrated crop-livestock system; both studies also found that the 0.00-0.10 m layer presented the highest variations and consequently needed a larger number of subsamples than any other soil layer to achieve a good level of reliability. However, considering that the surface layer of the soil under a no-tillage system is periodically disturbed during crop sowing, which minimizes possible physical restrictions to plant root growth, the decision of the subsample numbers per sampling point to provide penetration resistance measurements should be based on the microvariability of this parameter in the deeper soils layers (Moreira et al, 2016).…”
Section: Quality Of the Thematic Spr Maps In The Function Of The Numbmentioning
confidence: 99%
“…The SPR is usually quantified using traditional sampling methods, which include the collection of various subsamples (e.g., 12-15) in a random manner along the field and are considered independent samples (Tavares-Filho & Ribon, 2008;Storck et al, 2016). As a result, a mean SPR value is obtained for and applied to the total sampled area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation